2023
DOI: 10.3390/jpm13030547
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Networks Can Create High Quality Artificial Prostate Cancer Magnetic Resonance Images

Abstract: The recent integration of open-source data with machine learning models, especially in the medical field, has opened new doors to studying disease progression and/or regression. However, the ability to use medical data for machine learning approaches is limited by the specificity of data for a particular medical condition. In this context, the most recent technologies, like generative adversarial networks (GANs), are being looked upon as a potential way to generate high-quality synthetic data that preserve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, they also found that for younger radiologists, this resulted in an improved ability to detect PCa. However, Xu and colleagues 105 found that a blinded radiologist did not find the quality of their synthetic images to be inferior to those non-processed.…”
Section: Ai For Image Acquisitionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, they also found that for younger radiologists, this resulted in an improved ability to detect PCa. However, Xu and colleagues 105 found that a blinded radiologist did not find the quality of their synthetic images to be inferior to those non-processed.…”
Section: Ai For Image Acquisitionmentioning
confidence: 98%
“…Deep learning has also been used in the emerging field of synthetic MRI, where generative adversial models create images based on acquired data. 105 Hu and colleagues 106 compared acquired DWI images to those modified by their model and found improved image quality with reduced distortion and artifacts. In addition, they also found that for younger radiologists, this resulted in an improved ability to detect PCa.…”
Section: Ai For Image Acquisitionmentioning
confidence: 99%
“…In the context of PCa, these algorithms can be trained on data from tissue samples, medical images, and other clinical information to identify patterns and features associated with the disease [62][63][64][65][66][67][68][69][70][71][72] . Machine learning has proven to be particularly effective in the automated analysis of medical images, including MRI scans and biopsy slides [73][74][75][76][77][78][79][80][81][82] . These algorithms can accurately detect suspicious areas of the prostate and provide a more precise diagnosis than traditional manual analysis.…”
mentioning
confidence: 99%